Monocyte/macrophage inflammatory response pathways to combat Francisella infection: possible therapeutic targets? - Gillette, Devyn D.; Tridandapani, Susheela; Butchar, Jonathan P. (Frontiers in Cellular and Infection Microbiology, 2014)
Francisella tularensis can bypass and suppress host immune responses, even to the point of manipulating immune cell phenotypes and intercellular inflammatory networks. Strengthening these responses such that immune cells more readily identify and destroy the bacteria is likely to become a viable (and perhaps necessary) strategy for combating infections with Francisella, especially given the likelihood of antibiotic resistance in the foreseeable future. Monocytes and macrophages offer a niche wherein Francisella can invade and replicate, resulting in substantially higher bacterial load that can overcome the host. As such, understanding their responses to Francisella may uncover potential avenues of therapy that could promote a lowering of bacterial burden and clearance of infection. These response pathways include Toll-like Receptor 2 (TLR2), the caspase-1 inflammasome, Interferons, NADPH oxidase, Phosphatidylinositide 3-kinase (PI3K), and the Ras pathway. In this review we summarize the literature pertaining to the roles of these pathways during Francisella infection, with an emphasis on monocyte/macrophage responses. The therapeutic targeting of one or more such pathways may ultimately become a valuable tool for the treatment of tularemia, and several possibilities are discussed.